Respuesta :

[tex]x^4\dfrac{\mathrm dy}{\mathrm dx}+x^3y=-\sec(xy)[/tex]

Divide both sides by [tex]x^3[/tex]:

[tex]x\dfrac{\mathrm dy}{\mathrm dx}+y=\dfrac{\mathrm d}{\mathrm dx}[xy]=-\dfrac{\sec(xy)}{x^3}[/tex]

Integrate both sides to get

[tex]xy=y_0=\displaystyle\int_{x_0}^x\frac{\sec(ty)}{t^3}\,\mathrm dt[/tex]

where [tex]x_0[/tex] and [tex]y_0=y(x_0)[/tex] are constants, and divide by [tex]x[/tex] to solve for [tex]y(x)[/tex]:

[tex]\boxed{y(x)=\dfrac{y_0}x+\displaystyle\frac1x\int_{x_0}^x\frac{\sec(ty)}{t^3}\,\mathrm dt}[/tex]

An exact solution (not in terms of a definite integral, anyway) doesn't seem likely...